Dealing with emotional problems in coaching : a rational-emotive and cognitive-behavioural approach - Dryden, Windy (London ; New York : Routledge, Taylor & Francis Group, 2021)
"This book is a comprehensive guide for coaches on how to use Rational-Emotive and Cognitive Behaviour Therapy to help coachees with their emotional problems within a coaching context. In this fully updated new edition, Windy Dryden: Discusses the eight major emotions that feature in coachees' emotional problems and their healthy alternatives, Outlines a step-by-step guide to the use of RECBT in the coaching context, Illustrates these points with a case of a coachee whose progress towards a personal development objective was hampered by an emotional problem and how the coach implemented RECBT to help her deal with obstacle and resume development-based coaching Dealing with Emotional Problems in Coaching will be a valuable resource for all those involved in coaching"--
Earlier edition published as: Dealing with clients' emotional problems in life coaching.
OCLC-licensed vendor bibliographic record.
Keywords: Personal coaching; Rational emotive behavior therapy; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health